PERAN NILAI TAWAKAL SEBAGAI PERBAIKAN MENTAL PADA ANAK, TELAAH TAFSIR MAFÂTIH AL-GHAIB KARYA FAKHRUDDIN AR-RAZI - Shofa, Nur Yusuf (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This article aims to explain the concept of tawakkul (trust in God) based on Fakhruddin ar-Razi’s interpretation in Mafâtih al-Ghaib and its relevance to developing children’s character today. The method used is library research with a thematic interpretation of verses about tawakkul, supported by Ar-Razi’s explanation. The results show that tawakkul is not about doing nothing, but about trying seriously and then leaving the results to Allah. For children today, this concept is helpful to face problems like peer pressure, feeling unappreciated after doing good, the temptation to cheat, or feeling hurt when betrayed. The discussion proves that tawakkul can help children become more honest, patient, and confident, and it makes their mindset stronger. Therefore, Ar-Razi’s view on tawakkul is not only spiritual, but also educational and practical. In conclusion, understanding tawakkul in a modern way is important to build strong and positive character in children today.